До характеристики порядку застосування заохочень до працівників поліції - Іванюк, Б. А.; Ivaniuk, B. A. (Правові новели. - 2022. - № 18. - С. 27-32, 2022)
Надано характеристику загальному порядку застосування заохочень до працівників Національної поліції України. Акцентовано увагу на існуванні особливостей при застосуванні окремих видів заохочень до працівників поліції. Визначено та охарактеризовано спеціальний порядок застосування окремих різновидів заохочень до працівників Національної поліції. З’ясовано, що власними відмінно стями характеризується також порядок заохочення працівників Національної поліції України грошовою винагородою. Наголошено, що загальний порядок застосування заохочень до працівників Національної поліції України являє собою процес виконання послідовних дій, розподілених на три етапи, а саме: 1) формування подання керівника в якому вказуються всі відомості, що обґрунтовують необхідність, доцільність та результативність заохочення відповідного працівника Національної поліції; 2) аналіз матеріалів про заохочення на предмет правильності їх оформлення, а також достовірності закріплених у них відомостей; 3) оформлення та підписання уповноваженим керівником управлінського акту – наказу про заохочення працівника поліції. Зроблено висновок, Зазначено, що поряд із загальним процесом дисциплінарного стимулювання працівників Національної поліції України, існує велика кількість відмінностей пов’язаних із специфікою окремо взятих різновидів заохочень. Спеціальний порядок застосування заохочень до працівників поліції має передбачати: 1) особливі вимоги щодо суб’єктного складу застосування заохочення, або особи поліцейського та його трудоправового статусу; 2) відмінний від загального порядок оформлення наказу про застосування заохочення; 3) відмінний від загального порядок оформлення подання про заохочення працівника Національної поліції України; 4) особливі вимоги щодо безпосереднього моменту застосування заохочення, зокрема, вручення нагороди в урочистій обстановці.

The article, based on the analysis of the norms of the current legislation, describes the general procedure for applying incentives to employees of the National Police of Ukraine. Attention is focused on the existence of peculiarities in the application of certain types of incentives to police officers. The special procedure for applying certain types of incentives to the employees of the National Police is defined and characterized. It was found that the procedure for encouraging employees of the National Police of Ukraine with monetary rewards is also characterized by its own differences. First of all, the monetary reward is paid within the limits of the appropriations provided for in the budget of the National Police of Ukraine, the relevant body (subdivision) of the police for the financial support of policemen and the wages of employees. It is emphasized that the general procedure for applying incentives to employees of the National Police of Ukraine is a process of performing consecutive actions divided into three stages, namely: 1) the formation of a manager's submission in which all information justifying the necessity, expediency and effectiveness of the incentive of the relevant employee of the National Police is indicated; 2) analysis of incentive materials for the correctness of their registration, as well as the reliability of the information contained in them; 3) drawing up and signing by the authorized manager of a management act - an order on the encouragement of a police officer. It was concluded that along with the general process of disciplinary incentives for employees of the National Police of Ukraine, there are a large number of differences related to the specifics of individual types of incentives. Therefore, the special procedure for applying incentives to police officers should provide for: 1) special requirements regarding the subject composition of the incentive application, or the person of the police officer and his labor law status; 2) different from the general procedure for drawing up an order on the application of incentives; 3) different from the general procedure for filing a submission on the promotion of an employee of the National Police of Ukraine; 4) special requirements regarding the immediate moment of application of the incentive, in particular, the presentation of the award in a solemn setting.

Дана характеристика общему порядку применения поощрений к работникам Национальной полиции Украины. Акцентировано внимание на существовании особенностей при применении отдельных видов поощрений к работникам полиции. Определен и охарактеризован специальный порядок применения отдельных разновидностей поощрений к работникам Национальной полиции.
To characterize the procedure for applying incentives to police officers
Keywords: Національна поліція України; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; поліцейські; police officers; полицейские; заохочення; promotion; поощрение; порядок застосування заохочень; procedure for applying incentives; порядок применения поощрений; Україна; Ukraine; Украина